" صورة المرأة في الخطاب النبوي في كتاب " رياض الصالحين : دراسة أسلوبية - بينج، ما تينج (Kuala Lumpur: Kulliyyah of Islamic Revealed and Human Sciences, IIUM, 2021)
The hadith is the second source of Islamic law, and it is the detailed standards and important guidelines for all aspects of Muslim’s life. This research aims to clarify the stylistic elements in the prophetic discourse related to women in the book "Riyad Al-Salihin", and to show the connotations and contexts that characterize these elements, depending on the descriptive and analytical methodology. The study concluded the following: Stylistics is one of the most important approaches in studying texts, and modern study within the framework of stylistics opens broad horizons for us in deducing the beauty of the prophetic discourse, its masterpieces and rulings related to women, her responsibilities towards Allah Almighty, and her husband, and the audio study contributes to revealing the aesthetics of prophetic rhetorical expression and helps. The repetition of sounds and words and their consistency with the atmosphere in which they are called and the function they perform in each context is to increase the musical and aesthetic rhythm of the prophetic discourse. Expressions related to women are also characterized by health, eloquence, ingenuity and cleverness, and their roles in clarifying and clarifying meanings and purposes in the last, most beautiful, best, best and optimal methods and means, and enhancing people’s understanding and mastery of honorable hadiths.